Evaluation of Aceclofenac Loaded Agarose Beads Prepared by Ionotropic Gelation Method (Stamford Journal of Pharmaceutical Sciences, 2009)
Aceclofenac loaded agarose beads were prepared by ionotropic gelation method and drug release profile, swelling index (SI %) and entrapping efficiency (EE %) of aceclofenac were investigated. The drug was dissolved in melted 4 % agar solution in different ratios. Beads were prepared by dropping the hot aqueous solution into a beaker of different percentages of chilled CaCl2 solution followed by filtering the solution and drying at room temperature. The entrapment efficiency was 100Â±5 %. The swelling index was found to be highest (18.22 % in 4 hours) for beads containing aceclofenac-agar (1:2) in 4 % electrolyte solutions and the swelling property was decreased with increasing electrolyte concentration. In vitro dissolution of beads was carried out in USP apparatus-II (paddle method) at 75 rpm. The drug release was measured by using UV-Spectrophotometer at Î»max of 268 nm for acid media and 274 nm for buffer media. The dissolution data were treated with zero order, first order and Higuchi model. Half of the formulations were fitted to Higuchi model and rest half to first order model. Finally it can be concluded that with the increasing polymer (agar) concentration, the release rate of aceclofenac was decreased and swelling index was increased and with the increasing electrolyte concentration, the release rate was increased and swelling index was decreased. Key Words: Aceclofenac, Agarose bead, Electrolyte, Ionotropic Gelation method. Â  doi:10.3329/sjps.v1i1.1780 S. J. Pharm. Sci. 1(1&2):10-17